Gold Nanocages with a Long Surface Plasmon Resonance Peak Wavelength as Contrast Agents for Optical Coherence Tomography Imaging at 1060 nm - Yongping Chen; Jiefeng Xi; Vinh Nguyen Du Le; Jessica Ramella-Roman; Xingde Li (Nanomaterials)
There is growing interest in optical coherence tomography (OCT) imaging at a wavelength of 1060 nm. However, potential contrast agents for OCT imaging at this specific wavelength has not been thoroughly investigated. In this study, we present the synthesis and optical characterization of gold nanocages with a small edge length (~65 nm) and a surface plasmon resonance peak around 1060 nm. These nanocages represent a class of potential contrast agents for OCT at 1060 nm. OCT imaging experiments were conducted on phantoms and in vivo mouse tissues using a 1060 nm swept-source OCT system, demonstrating significant enhancement in imaging contrast due to the presence of the gold nanocages.